An evaluation of the dramatic effectivity displayed by D.T. Mtywaku in two Xhosa dramas - Swart, Derek Adriaan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1991.